Platelet‐leucocyte aggregation is augmented in cirrhosis and further increased by platelet transfusion - Støy, S.; Patel, V. C.; Sturgeon, J. P.; Manakkat Vijay, G. K.; Lisman, T.; Bernal, W.; Shawcross, D. L. (Alimentary pharmacology & therapeutics, 2018)
Summary Background Thrombocytopenia and circulating dysfunctional immune cells are commonly observed in patients with cirrhosis. Platelets may form complexes with neutrophils, monocytes and T cells modulating their function. We recently reported increased frequencies of platelet‐complexed neutrophils in cirrhosis with evidence of neutrophil activation upon contact with healthy platelets in vitro. Whether this occurs in vivo following platelet transfusion and contributes to systemic inflammation and endothelial activation is unknown. Aims To characterise platelet‐leucocyte aggregation in cirrhosis and to determine whether elective platelet transfusion results in perturbations associated with changes in markers of haemostasis, inflammation or endothelial activation. Methods We collected blood from cirrhotics (n = 19) before and following elective platelet transfusion. We measured platelet‐leucocyte aggregation, activation and function, and markers of platelet activation, systemic inflammation and endothelial activation by flow cytometry. Haemostasis was assessed by thromboelastometry and plasma haemostatic proteins. Results We observed a 2.5‐fold increase in platelet‐complexed neutrophils in patients with cirrhosis compared with healthy subjects and twofold more platelets attached per monocyte and T cell. All platelet‐complexed leucocytes expressed higher levels of activation markers and platelet‐complexed neutrophils had higher resting oxidative burst and phagocytic capacity than their nonplatelet‐complexed counterparts (P < 0.001); most pronounced in patients with cirrhosis. Paradoxically, platelet‐complexed leucocyte frequency decreased with increasing MELD score. Platelet transfusion increased soluble CD40 ligand (platelet activation marker), the frequency of platelet‐complexed monocytes (P < 0.05) and improved haemostatic status. Conclusion Cirrhotic patients have activated circulating platelet‐complexed leucocytes with increased platelet‐monocyte aggregation following elective platelet transfusion. Elective platelet transfusion might therefore exacerbate immune dysfunction in cirrhosis. Linked ContentThis article is linked to Patel and Muir, and Støy and Shawcross papers. To view these articles visit https://doi.org/10.1111/apt.14654 and https://doi.org/10.1111/apt.14671.